بذل المجہود فی حل سنن ابی داؤد کا تعارف اور شروح ابی داؤد میں مقام، ایک تحقیقی جائزہ: An Introduction to "Al Bazl ul Majhood" and its significance in Sunan Abi Dawood’s Interpretations - Dr Muhammad Inamullah; Muhammad Waliullah; Muhammad Sanaullah (Al Manhal Research Journal, 2023)
Bazl ul Majhood is a great interpretation of Sunan Abi Dawud written by Moalana KhalilAhmad Saharanpuri a great muhaddith , commentator and jurist of the Indian sub-continent,as well as a high ranking and great Sufi. In this Book, Mulana Khalil Ahmad Saharanpuri has mentioned in detail all the relevant jurisprudential discussions along with the interpretation of the Hadiths.In the same way,all the discussions of Hadith principles have also been explained in detail.This article attempts to provide an introduction sto this useful book and a research review in its significance.